Rubber Tire Dust-Rice Husk Pyramidal Microwave Absorber - Hassan, Nornikman; Cheng, Ee Meng; O. Nadiah; Abd Malek, Mohd Fareq; Manjur Ahmed; Abd. Aziz, Mohamad Zoinol Abidin; Othman, Abdul Rani; Soh, Ping Jack; Abdullah Al-Hadi, Azremi; A. Hasnain; Taib, Mohd Nasir (EMW Publishing, 2011)
Rubber tire dust-rice husk is an innovation in improving the design of pyramidal microwave absorbers to be used in radio frequency (RF) anechoic chambers. An RF anechoic chamber is a shielded room covered with absorbers to eliminate unwanted refection signals. To design the pyramidal microwave absorber, rice husk will be added to rubber tire dust since the study shows that both have high percentages of carbon. This innovative material combination will be investigated to determine the best reflectivity or reflection loss performance of pyramidal microwave absorbers. Carbon is the most important element that must be in the absorber in order to help the absorption of unwanted microwave signals. In the commercial market, polyurethane and polystyrene are the most popular foam- based material that has been used in pyramidal microwave absorber fabrication. Instead of using chemical material, this study shows that agricultural waste is more environmentally friendly and has much lower cost. In this paper, three combinations of rubber tire dust and rice husk are fabricated to investigate the performance of microwave absorber reflection loss in operating in the frequency range from 7 GHz to 12 GHz.